1959
DOI: 10.1051/parasite/1959345623
|View full text |Cite
|
Sign up to set email alerts
|

Addenda à « Cours d’Helminthologie I. — Trématodes, Sous-Classe Aspidogastrea »

Abstract: Je crois utile, au point de vue de la distribution géographique des Aspidogaster, d'ajouter les références ci-après : A. Pologne. Au environs de Varsovie, Aspidogaster conchicola K. E. von Baer a été mentionné chez Unio pictorum (L.) par D. F. Sinitzin (1905, p. 3), dans « Matériaux pour l'histoire natu relle des Trématodes. Distomes des poissons et des grenouilles des

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Although the posterior sucker (incipient ventral disc) of the cotylocidium initially resembles the ventral/posterior sucker of digeneans, it subsequently undergoes subdivision into numerous alveoli. Our TEM studies tend to support the early ideas of Burmeister (1856), Monticelli (1892), Furhmann (1928), Faust (1932), Faust and Tang (1936), Chauhan (1954) and Dollfus (1958) for treating the Aspidogastrea as a separate group occupying an intermediate position between the Monogenea and the Digenea (Timofeeva 1975(Timofeeva , 2005Poddubnaya et al 2011Poddubnaya et al , 2012. Rohde (1972) also indicated that the Aspidogastrea seem to combine features of both monogeneans and digeneans.…”
Section: Comments On the Phylogenetic Implications Of The Morphogenetsupporting
confidence: 56%
See 1 more Smart Citation
“…Although the posterior sucker (incipient ventral disc) of the cotylocidium initially resembles the ventral/posterior sucker of digeneans, it subsequently undergoes subdivision into numerous alveoli. Our TEM studies tend to support the early ideas of Burmeister (1856), Monticelli (1892), Furhmann (1928), Faust (1932), Faust and Tang (1936), Chauhan (1954) and Dollfus (1958) for treating the Aspidogastrea as a separate group occupying an intermediate position between the Monogenea and the Digenea (Timofeeva 1975(Timofeeva , 2005Poddubnaya et al 2011Poddubnaya et al , 2012. Rohde (1972) also indicated that the Aspidogastrea seem to combine features of both monogeneans and digeneans.…”
Section: Comments On the Phylogenetic Implications Of The Morphogenetsupporting
confidence: 56%
“…Although some species can complete their life-cycle in one and the same mollusc, most exhibit a simple two-host lifecycle pattern. The vertebrate hosts are freshwater teleosts, and occasionally turtles, in the case of the Aspidogastrida and chondrichthyans in the case of the Stichocotylida (Aubert 1855;Voeltzkow 1888a, b;Monticelli 1892;Williams 1942;Brinkmann 1957;Dollfus 1958;Rohde 1972Rohde , 2001. Rohde (1972Rohde ( , 2001, in his major reviews of the biology and relationships of the Aspidogastrea, has considered that a closer examination of this group may shed more light on its phylogenetic affiliations with other platyhelminth groups.…”
Section: Introductionmentioning
confidence: 99%
“…Characters were coded based on discussions in Gibson (1987 ), Brooks et al . (1989); see also Brooks & McLennan (1993a) and Pearson (1992) and the following primary literature, confirmed by examination of specimens of selected available taxa: Aspidogaster conchicola (Bakker & Davids 1973; Dollfus 1958; Faust 1922; Huehner & Etges 1977; Stafford 1896; Williams 1942); Aspidogaster (Rai 1964; Rawat 1948); Cotylogaster michaelis (Monticelli 1892); Cotylogaster basini (Hendrix & Overstreet 1977); Cotylogasteroides occidentalis (Fredericksen 1980; Nickerson 1902) Cotylogasteroides barrowi (Huehner & Etges 1972); Cotylaspis (Osborn 1904; Rumbold 1928; Cho & Seo 1977); Lissemysia (Agrawal 1978; Sinha 1935; Tandon 1948; Singh & Tewari 1985); Lobatostoma (Caballero y Caballero & Hollis 1965; Zylber & Ostrowski de Nuñez 1999; Oliva & Carvajal 1984; MacCallum & MacCallum 1913); Lobatosoma manteri (Rohde 1973); Lobatosoma hanumanthai (Narasimhulu & Madhavi 1980); Lophotaspis interiora (Hendrix & Short 1972; Ward & Hopkins 1931); Lophotaspis vallei (Stossich 1899; Wharton 1933); Lophotaspis orientalis (Faust & Tang 1936); Multicalyx (Stunkard 1962; Thoney & Burreson 1987, 1988); Multicotyle purvisi (Dawes 1941; Rohde 1972); Rohdella siamensis (Gibson & Chinabut 1984); Rugogaster (Schell 1973; Amato & Pereira 1995); Stichocotyle nephropis (Nickerson 1895); Sychnocotyle kholo (Ferguson et al . 1999).…”
Section: Methodsmentioning
confidence: 76%
“…Lophotaspis vallei and Lophotaspis interiora have a single testis with two vas efferentia, which we have coded as two testes. Dollfus (1958) reported Aspidogaster conchicola as having a second rudimentary testis and therefore we have coded it as having two testes. Genital sac: present, enclosing pars prostatica and prostatic cells (0); absent (1); present, enclosing pars prostatica with prostatic cells both internal and external (2); present inclosing only the pars prostaica with prostatic cells external (3); enclosing prostatic cells but pars prostatica absent (4); pars prostatica and prostatic cells external to genital sac (5). Genital sac inclosing terminal end of uterus: absent (0); present (1). Cirrus: present (0); absent (1). Metraterm: present (0); absent (1). Vitellaria: interrupted posteriorly (0); not interrupted posteriorly (1). Vitellaria: interrupted anteriorly (0); not interrupted anteriorly (1). Vitelline ducts: paired (0); single (asymmetrical) duct (1). Vitellaria: follicular (0); compact (as cord) (1). Common vitelline duct: opening between ovary and Mehlis’ gland (0); opening at Mehlis’ gland (1). Orientation of ovary: oviduct opening posteriorly (0); opening anteriorly (1). Ootype: posterior to ovary (0); anterior to ovary (1). Proximal portion of uterus: passing posteriorly (0); passing anteriorly (1). Laurer's canal: present, proceeding posteriorly, opening externally or not (0); absent (1); present, proceeding anteriorly, opening externally (2). Agarwal (1978) states that a Laurer's canal is present without any further information regarding this structure.…”
Section: Methodsmentioning
confidence: 99%
“…Although the organ that character 25 refers to is not a pharynx but an oesophageal bulb (see Pharynx under Cercaria), the question which position of the pharynx is plesiomorphic is still of interest as in some digeneans, such as Heronimus, the pharynx abuts the oral sucker and is separated from the caecal bifurcation by an oesophagus, whereas in others, such as Stephanostomum Looss, 1899, it is at the caecal bifurcation and is separated from the oral sucker by a long prepharynx. As there is no oesophagus in Brooks' outgroups, the Udonellidea and Temnocephalidea, and a short oesophagus in his sister group, the Aspidocotylea (Dollfus, 1958), position of pharynx at the caecal bifurcation is plesiomorphic, reversing the polarity of the above pair. The polarity of this series has been reversed by Brooks et al (1989), who said that presence of body spines is plesiomorphic, with which I agree.…”
Section: Head Collarsmentioning
confidence: 99%